Relationships Among Risk, Incentive Pay, and Organizational Performance - Bloom, Matt; Milkovich, George T. (Academy of Management Journal, 1998)
In this study, we extended agency-based research by examining the role of risk in the structure of managerial compensation and its relationship to organization performance. Our results suggest that organizations facing higher risk do not place greater emphasis on short-term incentives than other organizations?rather, they place less emphasis on them. Also, higher-risk firms that relied on incentive pay exhibited poorer performance than higher-risk firms that did not emphasize incentive pay.